Effect of sodium valproate on neural tube development in chick embryos (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Valproic acid is an antiepileptic drug prescribed as monotherapy in newly diagnosed cases of Epilepsy. It is also useful in combating generalized Tonic-Clonic Seizures, Partial Seizures, and Myoclonic Seizures. It acts by increasing the levels of the Neurotransmitter GABA in the cerebrum. Valproate inhibits sustained repetitive firing induced by depolarization of cortical or spinal cord neurons. It produces small reductions of the low-threshold (T) Calcium current at clinically relevant but slightly higher concentrations then limit sustained repetitive firing. Reducing T currents may contribute to the effectiveness of Valproic acid against partial and tonic–clonic seizures and absence seizures respectively. In vitro, Valproate can stimulate the activity of the GABA synthetic enzymes, Glutamic Acid Decarboxylase and inhibit GABA degradative enzymes, GABA transaminases. However, studies show that they cause defects in the formation of neural tube if used during pregnancy. In the present study fertilized eggs were administered with Sodium Valproate and the development of neural tube was studied after 21 days. The histological and gross features of neural tube were identified.